Nefarious presentism - Tallant, Jonathan; Ingram, David (Oxford University Press, 2015)
Presentists, who believe that only present objects exist, face a problem concerning truths about the past. Presentists should (but cannot) locate truth-makers for truths about the past. What can presentists say in response? We identify two rival factions: ‘upstanding’ and ‘nefarious’ presentists. Upstanding presentists aim to meet the challenge, positing presently existing truth-makers for truths about the past; nefarious presentists aim to shirk their responsibilities, using the language of truth-maker theory but without paying any ontological price. We argue that presentists should be nefarious presentists.